2015
DOI: 10.1051/shsconf/20151702005
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Leader Prestige on Subordinates’ Job Attitude and Behavior: mediation and moderation effects

Abstract: Abstract.To explore the problem of leader prestige Chinese is familiar with, an empirical study was conducted. Base on the results of a sample of full-time employees in enterprises, the present study analyzed the effects of leader prestige on subordinates' job attitude and behavior. The study proves that leader prestige can improve leader trust and organization identification of subordinates. Leader prestige can give birth to positive effects on leader trust, and then improve organizational identification of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Moreover, while there is a paucity of prior research on the topic, previous findings have identified a relation among leader prestige and various beneficial outcomes, such as supporting leadership opportunities (Cheng, 2020), positively influencing group decisions (van Kleef et al, 2021), and motivating cooperation among colleagues (Henrich et al, 2015). Leader prestige has also been found to improve employee's trust in leader, organizational commitment, and job satisfaction (Case & Maner, 2014;He et al, 2015). Furthermore, following an examination of leader prestige in a hierarchical institution (i.e., the military), Offord et al (2019) found that leaders high in prestige, regardless of rank, were able to disseminate information more efficiently compared to leaders low in prestige, suggesting that colleagues value and accept information coming from a prestigious leader, and behave accordingly.…”
Section: Leader Dominance and Prestigementioning
confidence: 99%
“…Moreover, while there is a paucity of prior research on the topic, previous findings have identified a relation among leader prestige and various beneficial outcomes, such as supporting leadership opportunities (Cheng, 2020), positively influencing group decisions (van Kleef et al, 2021), and motivating cooperation among colleagues (Henrich et al, 2015). Leader prestige has also been found to improve employee's trust in leader, organizational commitment, and job satisfaction (Case & Maner, 2014;He et al, 2015). Furthermore, following an examination of leader prestige in a hierarchical institution (i.e., the military), Offord et al (2019) found that leaders high in prestige, regardless of rank, were able to disseminate information more efficiently compared to leaders low in prestige, suggesting that colleagues value and accept information coming from a prestigious leader, and behave accordingly.…”
Section: Leader Dominance and Prestigementioning
confidence: 99%